Refractive index tuning and birefringence effect in crosslinked siloxane-acrylate copolymers for optical waveguide applications - Amir Muhammad Noh, Amin Abdul Rahman; Hazizan, Md Akil; Mohd Kamil, Abd Rahman; Noorlisa, Harun; Zulkifli, Ahmad (Elsevier, 2024)
Tunability of refractive index of polymeric waveguide material could be made by controlling free volume as well as polarizability of constituent materials. Two acrylate-co-polysiloxane series of different crosslinking network were synthesised by utilizing different crosslinker and monomer feeding ratio. Using Claussius-Mossotti/Lorentz-Lorentz (CM/LL) model, fractional free volumes were calculated showing a decrease in the experimental (nexp) compared to theoretical (ni) refractive indices. Curing agent with asymmetrical configuration induce a crosslink network of higher birefringence. They were respectively fabricated into multimode channel waveguide whose core-clad refractive index differences (Δn) show values in the range 0.0049–0.0408.